Math Is Fun Forum
  Discussion about math, puzzles, games and fun.   Useful symbols: ÷ × ½ √ ∞ ≠ ≤ ≥ ≈ ⇒ ± ∈ Δ θ ∴ ∑ ∫ • π ƒ -¹ ² ³ °

You are not logged in.

#1 2014-07-27 13:19:57

Gabrielle
Guest

Solving Systems of Equations Using Substitution Method and Elimination

8.
y = (1/2)x - 3
y = (3/2)x – 1

y = (1/2)x – 3
(3/2)x – 1 = (1/2)x – 3
              +1                +1
(3/2)x = (1/2)x – 4
(4/2)x = -4
2x = -4
x = -2

y = (3/2)x – 1
y = (3/2)-2 – 1
y = -3 – 1
y = -4
(-2, -4)




12.
4x + 3y = -15
y = x + 2

y = x + 2 (times equation by 3)
3y = 3x + 6

4x + 3y = -15

7x = -21
x = -3

y = x + 2
y = -3 + 2
y = -1
(-3, -1)



16.
y = -2x + 1
y = x – 5

0 = 3x + 6
3x = 6
x = 2

y = x – 5
y = 2 – 5
y = -3
(2, -3)


Im not sure what I did wrong for these.. my teacher keeps telling me this


#8 - Tell me what you did to get from the first step to the second. 

(3/2)x=(1/2)x-2

(4/2)x= -2

#12 - The work must show elimination. You have used substitution. Try again.

#16 - I don't see your elimination work.  Please look at the example that I provided in my last post to help you show your work for #12 and #16.

#2 2014-07-27 20:33:19

bob bundy
Moderator
Registered: 2010-06-20
Posts: 6,311

Re: Solving Systems of Equations Using Substitution Method and Elimination

hi Gabrielle,

8.
y = (1/2)x - 3
y = (3/2)x –what sign is missing here? 1

y = (1/2)x – 3
(3/2)x – 1 = (1/2)x – 3
              +1                +1
(3/2)x = (1/2)x – 4
(4/2)x = -4
2x = -4
x = -2

y = (3/2)x – 1
y = (3/2)-2 – 1
y = -3 – 1
y = -4
(-2, -4)




12.
4x + 3y = -15
y = x + 2

y = x + 2 (times equation by 3)
3y = 3x + 6        ........................A   

4x + 3y = -15   ..........................B

7x = -21
x = -3

y = x + 2
y = -3 + 2
y = -1
(-3, -1)

This answer is correct and it looks like you have used elimination.  You can make this clear by lettering the equations and then stating what you are doing to eliminate y.

eg A - B gives    3y - 4x - 3y = 3x + 6 - (-15)

-4x = 3x +21

etc



16.
y = -2x + 1
y = x wthat sign is missing here? – 5

0 = 3x + 6
3x = 6
x = 2

y = x – 5
y = 2 – 5
y = -3
(2, -3)


Im not sure what I did wrong for these.. my teacher keeps telling me this


#8 - Tell me what you did to get from the first step to the second. 

(3/2)x=(1/2)x-2

(4/2)x= -2

This step is wrong.  If you subtract (1/2)x from each side you should have x = -2

#12 - The work must show elimination. You have used substitution. Try again.

#16 - I don't see your elimination work.  Please look at the example that I provided in my last post to help you show your work for #12 and #16

Bob


You cannot teach a man anything;  you can only help him find it within himself..........Galileo Galilei

Offline

Board footer

Powered by FluxBB